UMPSA saves up to RM600,000 a year using solar power on its assets - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
KUANTAN, 29 November 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is now expected to reduce carbon dioxide (CO2) production of its Pekan campus by 47%, equivalent to savings in electricity bills between RM400,000 and RM600,000 per year thanks to the installation of solar panels with 3.58 MWp capacity.